Application of the principles of ruling determination in the prohibition of blood plasma in food - Mohd Izhar Ariff Mohd Kashim,; Nur Asmadayana Hasim,; Nurul Hafizah Mohd Nor,; Farah Ayuni Mohd Hatta,; Al-Shiha, Ahmed Abdel Rahman Abdel Aziz (Penerbit Universiti Kebangsaan Malaysia, 2024)
Blood plasma is one of the constituents of blood. It is used in food products today due to its rich protein content. Its purpose is to increase the chewiness and improve the texture of food products, especially in producing processed products such as meatballs and surimi. There needs to be clarity regarding the determination of blood plasma ruling, whether it follows the ruling principles established in Islam or not. Thus, this paper intended to apply the principle of determining the ruling of blood plasma in food products according to Islam. This qualitative study used expert interviews and literature review methods by referring to books and journals related to blood plasma. This study established four application principles in determining blood plasma ruling: the principle of halal and haram food, the principle of istihalah, the principle of maslahah, and the principle of darurah. The use of blood plasma is haram because it contradicts the requirements of Islamic sharia and thus opposes the principles of determining the ruling of food based on blood plasma. This study is relevant for authorities such as JAKIM’s Halal Hub to improve the existing system. Further, it benefits the manufacturers and the general public in preparing and choosing food according to the ruling principles set by Islam. Analyses related to the use of blood plasma in food products involving laboratory studies and fiqh research can also be carried out in the future.